Crystal structure of 2-(1H-pyrazol-3-yl-κN)pyridine-κN-bis(2-(2,4-difluorophenyl)pyridinato-κ2C,N)iridium(III) sesquihydrate, C30H18F4IrN5·1.5[H2O] - Abdul Latiff Aqilah; Chong Yan Yi; Mark-Lee Wun Fui; Kassim Mohammad B. (Zeitschrift für Kristallographie - New Crystal Structures, 2022)
C30H18F4IrN5·1.5[H2O], tetragonal, I41/a (no. 88), a = 37.5562(5) Å, b = 37.5562(5) Å, c = 9.2031(2) Å, V = 12980.7(4) Å3, Z = 16, Rgt(F) = 0.0312, wRref(F2) = 0.1166, T = 300(2) K.